2015
DOI: 10.1093/bib/bbv056
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of circulating microRNA expression data obtained by quantitative real-time RT-PCR

Abstract: The high-throughput analysis of microRNAs (miRNAs) circulating within the blood of healthy and diseased individuals is an active area of biomarker research. Whereas quantitative real-time reverse transcription polymerase chain reaction (qPCR)-based methods are widely used, it is yet unresolved how the data should be normalized. Here, we show that a combination of different algorithms results in the identification of candidate reference miRNAs that can be exploited as normalizers, in both discovery and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(235 citation statements)
references
References 56 publications
7
223
0
5
Order By: Relevance
“…and miR-1, miR-206 and miR-133b identified by Koutsoulidou and collaborators24. Normalization is a critical issue in all circulating miRNA studies26. Three normalizers were used, one exogenous (cel-miR-39) and two endogenous (miR-106a and miR-17-5p).…”
Section: Resultsmentioning
confidence: 99%
“…and miR-1, miR-206 and miR-133b identified by Koutsoulidou and collaborators24. Normalization is a critical issue in all circulating miRNA studies26. Three normalizers were used, one exogenous (cel-miR-39) and two endogenous (miR-106a and miR-17-5p).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we did not use miR-16, as in many studies conducted by others, since this miRNA is particularly susceptible to hemolysis. 25 In this pilot study, we identified five miRNAs with promising diagnostic power in plasma of melanoma patients at different stages of disease. Three of them, that is, miR-149-3p, miR-150-5p, and miR-15b-5p, were significantly up-regulated, while two, that is, miR-193a-3p and miR-524-5p, were significantly down-regulated in plasma of patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…External reference couldn’t correct for the other causes of variability such as the total concentration of miRNA fraction. Endogenous controls were required19. To our knowledge, no study has been involved in the evaluation of reference genes specific for serum miRNAs in osteoporosis.…”
mentioning
confidence: 99%